Factors in steer feeding - Johnston, Harry Wallace (My University, 1899)
Introduction: The subject of steer feeding is one of the most important in Kansas agriculture; and judging from the way it is frequently carried on, a study of a few factors in steer feeding will be no waste of time. We will say here, however, that this is not all original; we have obtained some of this material from a study of Henry’: Feed and Feeding”, and from the eleventh Biennial Report of the Kansas State Board of Agriculture. Animal. I. Advantages of the beef over other breeds for feeding. At this time, there is no doubt that for feeding we should have one of the beef breeds, Hereford, short-horn or Pold Angus; little preference being shown to either of these three. 1. In the beef breeds we have a higher percentage of dressed weight.
Citation: Johnston, Harry Wallace. Factors in steer feeding. Senior thesis, Kansas State Agricultural College, 1898.
Morse Department of Special Collections
Keywords: Feed; Water; Salt; Pens; Bedding; care and Handling; Theses; Manuscripts (documents)